Product Innovation of Islamic Financial Institutions - Agus Rojak Samsudin (International Journal of Nusantara Islam, 2016)
This article was composed from the fact that the presence of Sharia Financial Institutions (SFC) cannot be separated from the existence of Conventional Financial Institutions. Islamic Bank appeared in the midst of the conventional banking development. It certainly gives the impression product of Islamic Bank is seen as the imitation of conventional banking products. The historical analysis shows that the substantive function of banking operations has been practiced since the early days of Islam. Even the profit and lost sharing principle has been applied from transactions Islamic business transactions (Mu'amalah) in the ancient Arab, which has been explored in the modern era and also legitimized by the Fatwa of DSN MUI (National Sharia Council of Indonesian Ulama Council (NSC-ICU). This institution is often reinterpreting the concept of Islamic business, including the innovation of Islamic Banking products that are derived from the Quran, the Sunna, and Islamic Jurisprudence (al-Ijtihad).